Determinan Reviu Laporan Keuangan dan Implikasinya terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Bob Mustafa; Elsa Sari Yuliana (Eksos, 2019)
There are still many LKPD opinions in West Kalimantan that have not yet reached WTP opinion, even stagnating from year to year. In addition, the role and function of regional inspectorates in realizing the aspirations of regional governments to obtain WTP opinions that have not been optimal needs to be improved. This study tries to find out the influence of understanding of government accounting standards and understanding of internal control systems in the process of reviewing financial statements in supporting the quality of local government financial reports. This study aims to determine and analyze the influence of the auditor's understanding of accounting standards and internal control systems on the quality of government financial reports through the financial statement review process. This research proves that directly there is a significant influence of Understanding of Government Accounting Standards and Understanding of the Internal Control System towards the Financial Report Review Process. An understanding of the Internal Control System and the Financial Report Review Process has a significant effect on the Quality of Financial Statements. Meanwhile, the understanding of understanding of government accounting standards has no significant effect on the quality of financial statements.